PERILAKU SEKSUAL PRANIKAH MAHASISWA PADA SALAH SATU UNIVERSITAS DI KABUPATEN SUMBAWA - Aggasi, Abbyzar (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study wanted to find out more about the premarital sexual behavior of students at one of the universities in Sumbawa Regency and their handling efforts. This research is based on the rise of premarital sex cases by students that occurred at one University in Sumbawa Regency (interview with Bunga, one of the students). This becomes interesting because the University is a campus with a very thick religious nuances both among Lecturers and Students. The University's location in